2016
DOI: 10.1016/j.celrep.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Lipids Reprogram Metabolism to Become a Major Carbon Source for Histone Acetylation

Abstract: SUMMARY Cells integrate nutrient sensing and metabolism to coordinate proper cellular responses to a particular nutrient source. For example, glucose drives a gene expression program characterized by activating genes involved in its metabolism, in part, by increasing glucose-derived histone acetylation. Here, we find that lipid-derived acetyl-CoA is a major source of carbon for histone acetylation. Using 13C-carbon tracing combined with acetyl-proteomics, we show that up to 90% of acetylation on certain histon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
271
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 279 publications
(289 citation statements)
references
References 29 publications
5
271
2
1
Order By: Relevance
“…Indeed, in β-catenin-activated HCC, FAO efficiently feeds the electron transfer chain, producing ATP with no uncoupling, rendering them independent from glucose for ATP production. Aside from providing an obvious energy source, boosting FAO confers other advantages to tumour cells, and recent research has highlighted the role of FAO in nicotinamide adenine dinucleotide phosphate (NADPH)homeostasis32 33 and epigenetics modifications 34. Indeed, it has been shown that lipid-derived acetyl-CoA is the main substrate for histone acetylation leading to epigenetic alterations 34.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in β-catenin-activated HCC, FAO efficiently feeds the electron transfer chain, producing ATP with no uncoupling, rendering them independent from glucose for ATP production. Aside from providing an obvious energy source, boosting FAO confers other advantages to tumour cells, and recent research has highlighted the role of FAO in nicotinamide adenine dinucleotide phosphate (NADPH)homeostasis32 33 and epigenetics modifications 34. Indeed, it has been shown that lipid-derived acetyl-CoA is the main substrate for histone acetylation leading to epigenetic alterations 34.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from providing an obvious energy source, boosting FAO confers other advantages to tumour cells, and recent research has highlighted the role of FAO in nicotinamide adenine dinucleotide phosphate (NADPH)homeostasis32 33 and epigenetics modifications 34. Indeed, it has been shown that lipid-derived acetyl-CoA is the main substrate for histone acetylation leading to epigenetic alterations 34. In addition, FAO has been suggested to be a pathway that allows NADPH homeostasis for tumour cells under conditions of energetic stress, such as during phases of nutrient deprivation 35 36.…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot completely rule out the possibility that epigenetic mechanisms also contribute to impaired osteoblast differentiation due to Cpt2 deficiency. Much like glucose catabolism, intramitochondrial fatty acid metabolism generates acetyl-CoA that can contribute to chromatin acetylation (53). We plan to explore this possibility in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Relative changes in protein acetylation and protein abundance were determined by quantitative mass spectrometry as described previously (21). Briefly, mitochondrial proteins were digested with trypsin and the resulting peptides were labeled with 6-plex Tandem Mass Tags (TMT, Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%